Regulation of GLUT4 expression in denervated skeletal muscle - Jensen, Ellis B.; Zheng, Donghai; Russell, Robert A.; Bassel-Duby, Rhonda; Williams, R. Sanders; Olsen, Ann Louise; Dohm, G. Lynis (East Carolina University, 2009)
Denervation by sciatic nerve resection causes decreased muscle glucose transporter 4 (GLUT4) expression, but little is known about the signaling events that cause this decrease. Experiments were designed to test the hypothesis that decreased GLUT4 expression in denervated muscle occurs because of decreased calcium/CaMK activity, which would then lead to decreased activation of the transcription factors myocyte enhancer factor 2 (MEF2) and GLUT4 enhancer factor (GEF), which are required for normal GLUT4 expression. GLUT4 mRNA was elevated in mice expressing constitutively active CaMK isoform IV (CaMKIV) and decreased by denervation. Denervation decreased GEF binding to the promoter and the content of GEF in the nucleus, but there was no change in either MEF2 binding or MEF2 protein content. Expression of a MEF2-dependent reporter gene did not change in denervated skeletal muscle. To determine the domains of the GLUT4 promoter that respond to denervation, transgenic mice expressing the chloramphenicol acetyl transferase (CAT) reporter gene driven by different lengths of the human GLUT4 promoter were denervated. Using several different promoter/reporter gene constructs, we found that all areas of the GLUT4 promoter were truncated or missing, except for the MEF2 binding domain and the basal promoter. All of the GLUT4 promoter/CAT reporter constructs evaluated responded normally to denervation. Our data lead us to conclude that decreased CaMK activity is not the reason for decreased GLUT4 content in denervated muscle and that negative control of GLUT4 expression is not mediated through the MEF2 or GEF-binding domains. These findings indicate that withdrawal of a GEF- or MEF2-dependent signal is not likely a major determinant of the denervation effect on GLUT4 expression. Thus, the response to denervation may be mediated by other elements present in the basal promoter of the GLUT4 gene. Originally published in American Journal of Physiology - Regulatory, Integretive and Comparative Physiology Vol. 296, 2009.
Keywords: Denervation; Exercise; Myocyte enhancer factor 2; GLUT4 enhancer factor; Glucose